Serological relationship of tumor necrosis factor-inducing exoantigens of Plasmodium falciparum and Plasmodium vivax. - Bate, C A (1992)
Exoantigens of Plasmodium vivax-parasitized erythrocytes stimulated macrophages to secrete tumor necrosis factor, and antisera raised against the exoantigens inhibited this secretion. The antisera also inhibited the activity of Plasmodium falciparum and Plasmodium yoelii exoantigens, and conversely, antisera against the latter cross-reacted with the exoantigens of P. vivax.